Impact of scientific research on the international climate regime: the strategic niche of the emissions gap reports - Alcamo, Joseph; Olhoff, Anne; Höhne, Niklas (Frontiers in Climate, 2025)
In the Paris Climate Agreement of 2015, countries agreed to a two-track approach to emissions and climate targets. For emissions they agreed to voluntary national emission reduction commitments (pledges), and for climate, to hold global temperature increases to “well below 2°C above pre-industrial levels” with a major effort to “limit the temperature increase to 1.5°C.” But the Agreement does not address the possible disconnect between these two tracks nor answer the question: When summed together, are national commitments for reducing emissions sufficient for staying within the agreed-upon global temperature limits? In order to address this question, and fill an important niche in the climate regime, the Emissions Gap report series presents an annual analysis of the discrepancy between pledges to reduce national emissions and agreed-upon temperature limits. In this paper we use an established framework to assess the impacts of the report series. An example of its impact is that data and findings from the report have been used for several years by country delegations to Climate COPs to inform and/or justify national policies to reduce or limit greenhouse gas emissions. We conjecture that several factors contribute to the impacts of the report series. For example, it appears to provide an accepted neutral playing field for debating the sufficiency of national emissions commitments to meeting global temperature targets. Other factors include its timeliness in addressing a key international policy question, its contribution to framing the policy of “ambition-raising and stocktaking,” its impartial synthesis of results from many different scientific groups and high scientific quality, its usefulness as an awareness-raising tool, and its production by a major, credible international boundary organisation (UNEP), among other factors. In general, the Emissions Gap report series shows that research findings, if strategically targeted and presented, can fill an important information niche in the policy landscape and have a tangible positive influence on climate policymaking. Yet after all this, its ultimate impact is certainly more modest since after several report editions, the emissions gap remains wide.